Antecedents of Mobile Banking User Loyalty Factors - Mirandasari, Ni Made Indah; Martini, Ida Ayu Oka (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
The growth of a nation's economy cannot occur without the presence of strong financial institutions. The purpose of this research is to investigate a variety of factors that have an impact on the level of fidelity displayed by customers who use mobile banking. The trust of the business and the satisfaction of its customers are essential components. The research was conducted in a non-bank financial institution known as the Village Credit organization (LPD), which is situated in Kelan Traditional Village in Badung Regency in the province of Bali. The study included a total of 120 participants who were clients of LPD Kelan and regularly utilized Mobile Banking. The participants were chosen through the use of a straightforward random sampling method. The dissemination of surveys was done directly through the use of Google Forms as part of the process of data collection. Quantifying replies in the questionnaire is done using a scale that ranges from strongly disagreeing to strongly agreeing on a 1-10 point interval scale. For the purpose of this study, the Structural Equation Modeling-Partial Least Squares (SEM-PLS) methodology was applied to the data analysis, and the SmartPLS 3.2 program was utilized. The findings of this investigation indicate that all hypotheses have been confirmed. Client loyalty is directly and significantly influenced in a positive way by factors such as quality of service, trust in the provider, and overall level of happiness with the provider's offering. Conversely, the influence of trust and service quality on loyalty is mediated by customer satisfaction, resulting in a positive and significant impact. As a result, the level of satisfaction functions as an efficient mediator of the study model